We come from Napoli: the dialect in Liberato’s songs as an identity marker - Barco, Simone; Marra, Francesca (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
In the global public perception, Italian culture has always been strongly associated with music. Traditionally, Italian song lyrics have been characterized by a high diatopic variation, which means that authors tend to mix dialects and Italian in their songs. In the last few years the contemporary music setting, and particularly the independent scene, opened up to dialectal features, colloquialisms and slang. In the present paper, we will discuss the use of Neapolitan by Liberato, a rapper who achieved resounding success in Italy and abroad during the last two years through his musical experimentation, a smart marketing strategy and by concealing his identity to the public. The aim of this essay is to analyze Liberato’s lyrics in order to evaluate whether the dialect he uses reflects the contemporary Neapolitan youth slang. In addition, we will investigate whether the mixture of languages in Liberato points to propagate a clear cut identity or not.